2003
DOI: 10.1187/cbe.03-03-0014
|View full text |Cite
|
Sign up to set email alerts
|

Bioliteracy and Teaching Efficacy: What Biologists Can Learn from Physicists

Abstract: The introduction of the Force Concept Inventory (FCI) by David Hestenes and colleagues in 1992 produced a remarkable impact within the community of physics teachers. An instrument to measure student comprehension of the Newtonian concept of force, the FCI demonstrates that active learning leads to far superior student conceptual learning than didactic lectures. Compared to a working knowledge of physics, biological literacy and illiteracy have an even more direct, dramatic, and personal impact. They shape publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 29 publications
0
63
0
1
Order By: Relevance
“…We are extending the study reported here with the Conceptual Inventory of Natural Selection (CINS) (Anderson, Fisher, & Norman, 2002) to examine the influence of prior knowledge on learning evolution, and look forward to other researchers using this tool to examine different curricular strategies and questions similar to those we have addressed. Lawson (1983) stated that instructors must know if students lack essential prior declarative knowledge; the CINS and tools from the forthcoming Bioliteracy project (Klymkowsky, Garvin-Doxas, & Zeilik, 2003) will provide instructors with standardized devices for quantifying prior knowledge, similar to those available for physics and astronomy (e.g., Hestenes, Wells, & Swackhammer, 1992;Hufnagel, 2002, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…We are extending the study reported here with the Conceptual Inventory of Natural Selection (CINS) (Anderson, Fisher, & Norman, 2002) to examine the influence of prior knowledge on learning evolution, and look forward to other researchers using this tool to examine different curricular strategies and questions similar to those we have addressed. Lawson (1983) stated that instructors must know if students lack essential prior declarative knowledge; the CINS and tools from the forthcoming Bioliteracy project (Klymkowsky, Garvin-Doxas, & Zeilik, 2003) will provide instructors with standardized devices for quantifying prior knowledge, similar to those available for physics and astronomy (e.g., Hestenes, Wells, & Swackhammer, 1992;Hufnagel, 2002, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Taking physics as an example, it is expected that the spread of active learning pedagogies through other sciences will be accelerated by the development of instruments comparable to the FCI, designed to measure student comprehension of concepts deemed to be important for understanding each of the scientific disciplines. An initial version of a Chemistry Concepts Inventory (CCI) has appeared (Mulford and Robinson, 2002), and a collaborative effort to create a Biological Concept Inventory (BCI) is currently underway (Klymkowsky et al, 2003).…”
Section: Classroom Studiesmentioning
confidence: 99%
“…MCQs are particularly useful for the development of concept inventories and related diagnostic tests that aim to assess students' conceptual understanding. The prevalence of such tests is expanding and they include, for example, the BCI [5,6], the conceptual inventory of natural selection [11], as well as question banks focusing on photosynthesis [12], diffusion and osmosis [13], cellular transport [14], and visualized biochemical structures [15]. In addition, Khodor et al [16] have formulated a hierarchical biology concept framework (BCF) that shows the relationships between concepts, highlights concepts that are difficult for novices to learn, and demonstrates what concepts are important for teachers to assess.…”
Section: Instruments For Assessing Conceptual Understandingmentioning
confidence: 99%
“…In addition, Khodor et al [16] have formulated a hierarchical biology concept framework (BCF) that shows the relationships between concepts, highlights concepts that are difficult for novices to learn, and demonstrates what concepts are important for teachers to assess. Klymkowsky et al [5] are developing items for the BCI that can be used to assess students' conceptual understanding of the fundamental ideas in molecular, cell, and developmental biology. These authors view their inventory as a ''lever for moving our current educational system in a direction that delivers a deeper conceptual understanding of the fundamental ideas upon which biology and biomedical sciences are based'' (p. 155).…”
Section: Instruments For Assessing Conceptual Understandingmentioning
confidence: 99%
See 1 more Smart Citation